The Effect of Incentives and Work Stress on Employee Performance during the Covid-19 Pandemic at the Office of the Director of PT. Perkebunan Nusantara III - Fajar Rezeki Ananda Lubis (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of incentives and work stress on employee performance during the COVID-19 pandemic at the Office of the Director of PT. Nusantara Plantation III. This research was conducted at PT. Perkebunan Nusantara III, Medan. The number of samples in this study were 51 people. Data was collected using a questionnaire in accordance with the indicators of each variable used. The data obtained were then analyzed using multiple linear regression analysis. The results show that incentives and work stress simultaneously have a significant effect on employee performance during the COVID-19 pandemic. The results of the t test show that incentives and work stress have a significant effect on employee performance.